2021
DOI: 10.1007/s11427-021-1990-5
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide CRISPR activation screen identifies candidate receptors for SARS-CoV-2 entry

Abstract: The outbreak of coronavirus disease 2019 (COVID-19) caused by SARS-CoV-2 has created a global health crisis. SARS-CoV-2 infects varieties of tissues where the known receptor ACE2 is low or almost absent, suggesting the existence of alternative viral entry pathways. Here, we performed a genome-wide barcoded-CRISPRa screen to identify novel host factors that enable SARS-CoV-2 infection. Beyond known host proteins, i.e., ACE2, TMPRSS2, and NRP1, we identified multiple host components, among which LDLRAD3, TMEM30A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 55 publications
1
50
0
2
Order By: Relevance
“…Instead, we suppose that NTD mutations might modulate some functional properties of this domain, which unfortunately remains experimentally understudied. The described NTD functions include controlling S-protein conformation ( Li et al., 2021 ), interaction with host surface sialosides ( Awasthi et al., 2020 ) and, most recently, binding to alternative entry receptors ( Zhu et al., 2021 ). The second hot spot – the RBD domain shows a strong accumulation of mutations at the binding interface with the ACE2 receptor (see below for a dedicated paragraph).…”
Section: Resultsmentioning
confidence: 99%
“…Instead, we suppose that NTD mutations might modulate some functional properties of this domain, which unfortunately remains experimentally understudied. The described NTD functions include controlling S-protein conformation ( Li et al., 2021 ), interaction with host surface sialosides ( Awasthi et al., 2020 ) and, most recently, binding to alternative entry receptors ( Zhu et al., 2021 ). The second hot spot – the RBD domain shows a strong accumulation of mutations at the binding interface with the ACE2 receptor (see below for a dedicated paragraph).…”
Section: Resultsmentioning
confidence: 99%
“…This has included acquisition of the ability for heparin sulfate mediated infection of an ACE2-negative human lung epithelial as a result of the E484D mutation in the RBD(29), indeed in vitro evolution of SARS-CoV-2 to higher infectivity through more efficient binding to heparin sulfate has been reported(30), and in vivo reduction of intestinal ACE2 expression did not impact SARS-CoV-2 infection or severity(31), further suggesting the contribution of other cellular entry mechanisms. Several other receptors have been reported to facilitate ACE2-independent SARS-CoV-2 infection, including the tyrosine-protein kinase receptor UFO (AXL)(32), LDLRAD3, and CLEC4G(33). While it is almost certain that the current SARS-CoV-2 VoC ravaging humanity are highly dependent on ACE2, as the high level of viral burden among the world’s population continues, increasingly in people with pre-existing Abs to SARS-CoV-2 through prior infection or vaccination, S2 hmAbs may provide protection against possible future variations in attachment receptor utilization by CoV.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have confirmed that, in addition to ACE2 and CD147, SARS-CoV-2 can enter host cells by binding to some other receptors. Recent research hotspots include Cathepsin L1 ( Aguiar et al, 2020 ), integrins αvβ3 and αvβ6 ( Calver et al, 2021 ), and even low-density lipoprotein receptor class A domain containing 3 (LDLRAD3) and C- type lectin domain family 4 member G (CLEC4G) ( Zhu et al, 2021 ). The pathologic consequences of SARS-COV-2 binding to these receptors are uncertain.…”
Section: Introductionmentioning
confidence: 99%